2008
DOI: 10.1093/pcp/pcn009
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differentiation of Lotus japonicus TT2s, R2R3-MYB Transcription Factors Comprising a Multigene Family

Abstract: Leguminous plants have many paralogous genes encoding enzymes involved in the flavonoid biosynthetic pathway. Duplicate genes are predicted to contribute to the production of various flavonoid compounds and to have resulted in a diversity of legume species. We identified gene duplication in the transcription factors regulating flavonoid biosynthesis in the model legume Lotus japonicus. Three copies of a homolog of Arabidopsis thaliana TRANSPARENT TESTA2 (TT2), which is a MYB transcription factor that regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 68 publications
1
64
0
Order By: Relevance
“…The abundance of LjMYB136, LjMYB137, and LjMYB139 (subgroup 5) transcripts was very low in young leaves prior to elicitation, consistent with their proposed roles in positively regulating condensed tannin biosynthesis (Yoshida et al, 2008), and were undetectable in elicited samples after 40 PCR cycles. Yoshida et al (2008) reported the same trend for LjMYB136 and LjMYB139 gene expression after GSH treatment.…”
Section: R2r3myb Tfssupporting
confidence: 62%
“…The abundance of LjMYB136, LjMYB137, and LjMYB139 (subgroup 5) transcripts was very low in young leaves prior to elicitation, consistent with their proposed roles in positively regulating condensed tannin biosynthesis (Yoshida et al, 2008), and were undetectable in elicited samples after 40 PCR cycles. Yoshida et al (2008) reported the same trend for LjMYB136 and LjMYB139 gene expression after GSH treatment.…”
Section: R2r3myb Tfssupporting
confidence: 62%
“…R2R3-MYB TFs have been described to regulate PA biosynthesis, often in a complex with bHLH and WD40 proteins (Baudry et al, 2004;Yoshida et al, 2008Yoshida et al, , 2010Hichri et al, 2011), in a wide range of plants. In our study, ectopic expression of TaMYB14 under the control of the CaMV 35S promoter resulted in PA accumulation in leaves of N. tabacum, M. sativa, and T. repens without the need for coexpression of additional factors.…”
Section: Tamyb14 Is An R2r3-myb Tf Regulating Pa Biosynthesis In Legumesmentioning
confidence: 99%
“…Other species in which MYB TFs have been reported to be crucial for PA biosynthesis include Brassica napus, Diospyrios kaki (persimmon), and Populus tremuloides (Wei et al, 2007;Akagi et al, 2009;Mellway et al, 2009), indicating that MYB TFs are common regulators of PA biosynthesis. The first legume R2R3-MYB TFs reported to regulate PA biosynthetic genes are three Lotus japonicus TT2 orthologs, which, if coexpressed with AtTT8, AtTTG1, and LjANR in transient Arabidopsis leaf cell assays, activate the promoter of LjANR (Yoshida et al, 2008). Constitutive expression of LjTT2a results in the production and accumulation of PAs and anthocyanins in Arabidopsis seedlings and induces the expression of CHS, DFR, ANS, ANR, and a glutathione S-transferase predicted to be involved in PA monomer transport (Yoshida et al, 2010).…”
mentioning
confidence: 99%
“…Legume TF genes discovered in this way include those involved in the control of floral meristems, such as LjFLO, PsFLO/LFY, PsPEAM4, and MtPIM (Hofer et al, 1997;Berbel et al, 2001;Taylor et al, 2002;Dong et al, 2005;Benlloch et al, 2006). In the same way, three L. japonicus MYB TFs with homology to Arabidopsis TRANSPARENT TESTA2 (AtTT2) were shown to regulate proanthocyanidin biosynthesis after their transient expression in Arabidopsis leaves (Yoshida et al, 2008). More recently, the role of legume TF genes was investigated using reversegenetic approaches.…”
Section: Legume Tf Genes: What Is Known?mentioning
confidence: 99%